Address at the opening of the twenty-fifth session - Lawson, James A. (Statistical and Social Inquiry Society of Ireland, 1872)
As President of your Society, I have been called upon to discharge the usual duty of delivering the opening address from this chair. I take the opportunity of returning thanks for the honour conferred upon me, and of soliciting your kind indulgence for the omissions and imperfections which may be found in an address written amidst the pressure of very many absorbing duties. It has been not unusual for the president upon such occasions to take an opportunity of reviewing the condition of our country, regarded from an economic point of view, in order to estimate fairly our present state, to derive some lessons from the experience of the past, and encouragement or warning for the future.
Read before the Society, 21 November 1871
Keywords: 1871 Irish census; Irish agriculture; Economic conditions in Ireland in the late nineteenth century; Irish demographics; 314.15